COVID-19 Risk Appears to Vary Across Different Alcoholic Beverages - Dai, Xi-jian; Tan, Liang; Ren, Lina; Shao, Yuan; Tao, Weiqun; Wang, Yongjun (Frontiers in Nutrition, 2022)
Objectives: To evaluate the associations of status, amount, frequency of alcohol consumption across different alcoholic beverages with COVID-19 risk and associated mortality. Methods: This study included 473,957 subjects, 16559 of whom tested positive for COVID-19. Multivariate Logistic regression analysis was used to evaluate the association of alcohol consumption with COVID-19 risk and associated mortality. Non-linearity association between amount of alcohol consumption and COVID-19 risk was evaluated by a generalized additive model. Results: Subjects who consumed alcohol double above the guidelines had a higher risk of COVID-19 (1.12 [1.00, 1.25]). Consumption of Red wine above or double above the guidelines played protective effects against the COVID-19. Consumption of beer and cider increased the COVID-19 risk, regardless of frequency and amount of alcohol intake. Low-frequency of consumption of fortified wine (1-2 glasses/week) within guidelines had a protective effect against the COVID-19. High frequency of consumption of spirits (≥5 glasses/week) within guidelines increased the COVID-19 risk, whereas high frequency of consumption of white wine and champagne above the guidelines decreased the COVID-19 risk. The Ggeneralized additive model showed an increased risk of COVID-19 with a greater number of alcohol consumption. Alcohol drinker status, frequency, amount and subtypes of alcoholic beverages were not associated with COVID-19 associated mortality. Conclusions: The COVID-19 risk appears to vary across different alcoholic beverage subtypes, frequency and amount. Red wine and white wine and champagne appear to have chances to reduce the risk of COVID-19. Consumption of beer and cider and spirits, and heavy drinking are not recommended during the epidemics. Public health guidance should focus on reducing the risk of COVID-19 by advocating healthy lifestyle habits and preferential policies among consumers of beer and cider and spirits.